Irradiation-induced amorphization in the zirconium suboxide on Zr-0.5Nb alloys - Liu, J; He, G; Hu, J; Shen, Z; Kirk, M; Li, M; Ryan, E; Baldo, P; Lozano-Perez, S; Grovenor, C (Elsevier, 2018)
We report for the first time the observation of irradiation-induced amorphization of the zirconium suboxide formed during aqueous corrosion of Zr-0.5Nb alloys. High-resolution transmission electron microscopy results reveal amorphization of the hexagonal-ZrO suboxide under heavy ion irradiation at cryogenic temperatures. This irradiation-induced amorphization behaviour is discussed in relation to the arrangement of oxygen interstitials and the formation of stable superlattices. The sensitivity of the suboxide to irradiation damage can lead to phase changes and the accumulation of defects near the oxide/metal interface, which needs to be taken into account in the development of mechanistic models addressing radiation-assisted acceleration of corrosion rates in zirconium alloys.